THE LEGAL PHILOSOPHY OF ENVIRONMENTAL MANAGEMENT BASED ON PANCASILA JUSTICE - Mariane, Irene (Jurnal Pembaharuan Hukum, 2024)
Social justice in the environmental sector is a collective right, community empowerment in environmental management is a form of fulfilling community rights, especially communities whose areas have an impact on environmental exploitation. The aim of this research is to determine and analyze sustainable development in environmental protection and management in Indonesia, as well as to understand and analyze the legal philosophy of environmental management based on Pancasila justice. The approach method used in this research is normative legal research. The results of this research are the need for a holistic approach in environmental management and improving the quality of human resources to support sustainable environmental management, as well as integrating the principles of Pancasila with the concept of sustainable development and environmental management in Indonesia. Sustainable development aims to improve the quality and function of the environment, including its natural resources. The explanation, practice or application of Pancasila values in aspects of environmental management cannot be separated. The application of just and civilized human principles in everyday life can be realized in the form of concern for everyone's right to a good and healthy living environment; everyone's right to obtain environmental information relating to their role in environmental management; the right of every person to play a role in environmental management in accordance with applicable legal provisions